Infrared thermography and computed tomography imaging for hind limb study after immobilization-induced disuse atrophy - Martínez-Gutiérrez, Berenice; García-Pelagio, Karla P. (Frontiers in Imaging, 2024)
Immobilisation for treatment after an injury can lead to disuse atrophy, resulting in reduced functionality and strength of the immobilised limb. In our study, we utilized infrared thermography (IR) and computed tomography (CT) ex vivo to assess both physiological and structural changes following hind limb immobilisation in a young Wistar rat model. Twelve rats weighing 275 ± 30g had their right hind limbs immobilised with a modified Thomas-splint for varying durations (3, 7, or 14 days). IR imaging using an infrared camera provided insight into limb temperature changes. For micro-CT, we implemented a stain-ethanol fixation method and a grey score which enabled us to visualise and quantify muscle alterations. Thermographic images showed an increase in temperature of up to 8 % in the hind limb at supine position at 14 days due to the inflammatory process while micro-CT exhibited muscle shrinkage of 10% and 18% at 7 and 14 days, respectively. Our findings underscore the efficacy of IR and micro-CT as rapid and precise imaging modalities for detecting morphological shifts in muscle tissue, particularly in pathological conditions like atrophy.